2011
DOI: 10.1007/s00125-011-2110-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate high glucose-induced heparanase-1 production and heparan sulphate proteoglycan degradation in human and rat endothelial cells: a potential role in the pathogenesis of atherosclerosis

Abstract: Aims/hypothesis The content of heparan sulphate is reduced in the endothelium under hyperglycaemic conditions and may contribute to the pathogenesis of atherosclerosis. Heparanase-1 (HPR1) specifically degrades heparan sulphate proteoglycans. We therefore sought to determine whether: (1) heparan sulphate reduction in endothelial cells is due to increased HPR1 production through increased reactive oxygen species (ROS) production; and (2) HPR1 production is increased in vivo in endothelial cells under hyperglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Previously, we reported that kidney I/R induced ROS production that is inhibited by ET-1 deletion from endothelial cells (Arfian et al, 2012). Our results are consistent with several studies that reported about the role of ROS in mediating heparanase production, particularly in high glucose condition (Rao et al, 2011), as well as aldosteron and angiotensin II treatment in glomerulus (van den Hoven et al, 2009). Because of ROS has different role in the epithelial and interstitial cells after kidney I/R injury (Kim et al, 2010), it seem that heparanase also regulate those cells differently.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Previously, we reported that kidney I/R induced ROS production that is inhibited by ET-1 deletion from endothelial cells (Arfian et al, 2012). Our results are consistent with several studies that reported about the role of ROS in mediating heparanase production, particularly in high glucose condition (Rao et al, 2011), as well as aldosteron and angiotensin II treatment in glomerulus (van den Hoven et al, 2009). Because of ROS has different role in the epithelial and interstitial cells after kidney I/R injury (Kim et al, 2010), it seem that heparanase also regulate those cells differently.…”
supporting
confidence: 93%
“…Loss of glomerular endothelial glycocalyx in adriamycin nephropathy model associated with down regulation of HS and enzymes that play role in synthesis and elongation of proteoglycan GAG chains (Jeansson et al, 2009). HS loss is also induced by heparanase production, an endoglycosidase that degrades HS (Rao et al, 2011). In this study, we observed an increase of heparanase expression in extension phase of kidney I/R injury (Fig.3).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…They suggest that these changes may be associated with higher membrane fluidity and higher freedom in lateral movement thus allowing Apo B to acquire a conformation which is more favorable for proteoglycan binding. The heparin sulphate proteoglycans (HSPG) play an important role in the assembly and structure of the basement membrane [79]. There is evidence that HSPG is reduced under hyperglycaemic conditions [80].…”
Section: Atherosclerosis Formationmentioning
confidence: 99%
“…Loss of arterial heparin sulphate correlates with the onset of atherosclerosis in a monkey model of diabetes [81]. Recently, Rao et al, [79] have shown that hyperglycaemia induces heparin sulphate degradation through increase reactive oxygen production via increase in heparanase 1 which specifically degrades heparin sulphate proteoglycans thus a vicious circle is set up in which an increase in free radical production increases oxidation and Lp (a) aggregation and in turn stimulates inflammatory molecules such as tumor necrosis factor-(TNF ) and interleukan6 (IL-6) and increase free radical production. Heparanase-1 is produced locally by the endothelium.…”
Section: Atherosclerosis Formationmentioning
confidence: 99%